Community Structure of Mangrove Species in Bagakay Trail Lagoon, Claver, Surigao del Norte, Philippines - Bernales, Wegie; Guiritan, Faye Angela Dingding; Pecato, Crystal Jane Lopez; Mercado, Joel Andig; Tangonan, Jennifer Aquino; Calagui, Laurence Buque; Corbita, Victor Lobrigas (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Mangroves are highly valuable ecosystems that provide essential goods and services, including stabilizing coastlines, regulating water, supporting fisheries, and sequestering carbon. This study assessed the community structures of mangroves in Bagakay Trail Lagoon, Claver, Surigao del Norte. Four sampling stations with transect lines ranging from 150–200 m laid perpendicular to the shoreline were established. Additionally, five plots, each measuring 10 m × 10 m, were established at each station, with an interval of 20–30 m between plots. The mangrove leaf specimens were collected for proper identification of species. The study’s results identified thirteen mangrove species classified under nine families, all of which were categorized as least concern species based on the International Union for Conservation of Nature. The species diversity of the sampling area falls under very low diversity (H'=0.852), which may be attributed to anthropogenic activities and the recent typhoon Rai, which devastated the area. The most ecologically important species were Avicennia officinalis and Nypa fruticans, with high importance values suggesting their dominance and significant influence on the ecosystem. It is recommended that both government and non-government organizations implement site-specific conservation interventions to improve species diversity and ensure the sustainability of the mangrove ecosystem. Keywords: community structure, diversity indices, habitat assessment, mangroves, vegetation analysis